Sepse precoce de origem materna em uma unidade de terapia intensiva neonatal no Brasil: critérios diagnósticos, fatores de risco e evolução clínica - Barbosa, Nayara Gonçalves (2012)
Neonatal sepsis is the leading cause of morbidity and mortality mainly in developing countries, in which major proportion are maternally acquired. The purpose of this study was to investigate the incidence of early-onset sepsis (EOS) based on clinical and/or microbiological criteria, risk factors and outcome in a tertiary center in a Brazilian university hospital. We conducted a retrospectively study, case (infected) and control (no infected) model through consulting the medical chart records from mothers and newborn. Neonates admitted to the neonatal intensive care unit (NICU) and born at the University Hospital between January 2010 and December 2011were enrolled in our analysis and followed until discharge. We detected a high EOS incidence rate accounted for 110.91 cases per 1,000 live births and mainly of probable maternal origin (91.93%). This rate represented 37.80% of all sepsis occurred in NICU, with 38.7% of mortality, most of all within first week of life (75.9%). The majority of EOS diagnosis was based on clinical criteria (93.5%) in which in only one case was identified GBS; moreover, mothers colonization was unknown in 56.4% of cases. The risk factor associated to EOS identified at the present study was: vaginal delivery and 1-3 consults antenatal care. Thus, early-onset sepsis represents a greater contribution to the incidence of neonatal sepsis and represents a major burden in neonatal health assistance. We believe that simples and efficient efforts concerning several pre-natal practices and improving laboratorial diagnostics of maternal infections may have a greater impact in reducing neonatal mortality in developing countries like Brazil.